SCHEDULING OF EXAMINATION TERMS BASED ON PAST EXPERIENCE - Kalpic, Damir; Vanjak, Zvonimir; Baranovic, Mirta (International Journal of Computing, 2002)
A faculty with few thousand students, two studies and few hundred subjects faced the problem of how to devise the examination schedule. The aim of the examination schedule is to maximally disperse the examination terms as perceived by the students. Mixedinteger model turned out to be too complex and therefore genetic algorithm was applied. The achieved results were satisfactory enough to be accepted in the current academic year.